2006
DOI: 10.1021/ja0582298
|View full text |Cite
|
Sign up to set email alerts
|

Weakly Bound Water Molecules Shorten Single-Stranded DNA

Abstract: In this paper, we measure the single chain elasticity of an oligomer single-stranded DNA (ssDNA) in both aqueous and nonaqueous, apolar liquid environments by AFM-based single molecule force spectroscopy. We find a marked deviation between the force-extension relations recorded for the two conditions. This difference is attributed to the additional energy required to break the H-bond-directed water bridges around the ssDNA chain in aqueous solutions, which are nonexistent in organic solvents. The results obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
119
0
5

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 74 publications
(127 citation statements)
references
References 22 publications
3
119
0
5
Order By: Relevance
“…[31] A more recent study, which compared stretching in aqueous and nonpolar solvents, has also found evidence for extra stabilization associated with water bridges. [33] It is interesting to add that when polymers, including single-stranded DNA, are strongly stretched (with forces in the nanonewton range), bond angles can strongly deform. This implies using quantum chemical treatments to describe their behavior and also opens up the fascinating prospect of mechanically modulating chemical reactions.…”
mentioning
confidence: 99%
“…[31] A more recent study, which compared stretching in aqueous and nonpolar solvents, has also found evidence for extra stabilization associated with water bridges. [33] It is interesting to add that when polymers, including single-stranded DNA, are strongly stretched (with forces in the nanonewton range), bond angles can strongly deform. This implies using quantum chemical treatments to describe their behavior and also opens up the fascinating prospect of mechanically modulating chemical reactions.…”
mentioning
confidence: 99%
“…8a). It was found that there was a clear difference in the middle force regime, but no deviation in the low and high force regimes [31].…”
Section: Dnamentioning
confidence: 91%
“…The biological function of DNA is closely related to the stability and the integrality of the double strands [63], and the mechanical stability of double-stranded DNA (dsDNA) strongly depends on the ambient conditions. Recently, Cui et al investigated the important role of water in determining or stabilizing the supramolecular structure of DNA by SMFS [31,32].…”
Section: Dnamentioning
confidence: 99%
See 2 more Smart Citations